Brain networks underlying tactile softness perception : a functional magnetic resonance imaging study - Kitada, Ryo (2019)
Humans are adept at perceiving physical properties of an object through touch. Tangible object properties can be categorized into two types: macro-spatial properties, including shape and orientation; and material properties, such as roughness, softness, and temperature. Previous neuroimaging studies have shown that roughness and temperature are extracted at nodes of a network, such as that involving the parietal operculum and insula, which is different from the network engaged in processing macro-spatial properties. However, it is unclear whether other perceptual dimensions pertaining to material properties engage the same regions. Here, we conducted a functional magnetic resonance imaging study to test whether the parietal operculum and insula were involved in extracting tactually-perceived softness magnitude. Fifty-six healthy right-handed participants estimated perceived softness magnitude using their right middle finger. We presented three stimuli that had the same shape but different compliances. The force applied to the finger was manipulated at two levels. Classical mass-univariate analysis showed that activity in the parietal operculum, insula, and medial prefrontal cortex was positively associated with perceived softness magnitude, regardless of the applied force. Softness-related activity was stronger in the ventral striatum in the high-force condition than in the low-force condition. The multivariate voxel pattern analysis showed higher accuracy than chance levels and control regions in the parietal operculum/insula, postcentral gyrus, posterior parietal lobule, and middle occipital gyrus. These results indicate that a distributed set of the brain regions, including the parietal operculum and insula, is involved in representing perceived softness.